The Cambridge handbook of cognitive science - Frankish, Keith; Ramsey, William (William M.) (Cambridge : Cambridge University Press, 2012)
'Cognitive science is a cross-disciplinary enterprise devoted to understanding the nature of the mind. In recent years, investigators in philosophy, psychology, the neurosciences, artificial intelligence, and a host of other disciplines have come to appreciate how much they can learn from one another about the various dimensions of cognition. The result has been the emergence of one of the most exciting and fruitful areas of inter-disciplinary research in the history of science. This volume of original essays surveys foundational, theoretical, and philosophical issues across the discipline, and introduces the foundations of cognitive science, the principal areas of research, and the major research programs. With a focus on broad philosophical themes rather than detailed technical issues, the volume will be valuable not only to cognitive scientists and philosophers of cognitive science, but also to those in other disciplines looking for an authoritative and up-to-date introduction to the field'--
Machine generated contents note: Introduction; Part I. Foundations: 1. History and core themes; 2. The representational theory of mind; 3. Cognitive architectures; Part II. Aspects of Cognition: 4. Perception; 5. Action; 6. Human learning and memory; 7. Reasoning and decision making; 8. Concepts; 9. Language; 10. Emotion; 11. Consciousness; Part III. Research Programs: 12. Cognitive neuroscience; 13. Evolutionary psychology; 14. Embodied, embedded, and extended cognition; 15. Animal cognition; Glossary.
Includes bibliographical references and index.
Keywords: Cognitive science